Research on Image Encryption Algorithm Based on Matrix Scrambling and Matrix Product Transformation - Qin, Shu; Xu, Chunming (Journal of Computer Networks, Architecture and High Performance Computing, 2025)
This study introduces an innovative image encryption algorithm that leverages multiple rounds of matrix scrambling and matrix product transformation. Each round of encryption integrates cross-scrambling operations within the image matrix and invertible matrix product transformations, thereby effectively disrupting pixel positions and values. By iteratively adjusting pixel positions and transforming pixel values, the algorithm significantly enhances the security and robustness of the encryption process. The experimental results demonstrate that the proposed algorithm exhibits excellent resistance to statistical analysis, differential attacks, and other potential threats, thereby ensuring high security and practical applicability.